DISEASES OF ROOT CROPS - Khakimova Nigora Takhirovna; Sattarova Rano Kadirovna (Journals Park Publishing, 2024)
This article provides a comprehensive overview of diseases affecting root crops, including their impact, identification, prevention, and management strategies. Through literature analysis and discussion of methods, results, and conclusions, this article aims to enhance understanding and promote effective disease management in root crop cultivation.
Keywords: Root crops, Diseases, Pathogens, Management, Prevention, Crop health.